A constitutive model for various structural steels considering shared hysteretic behaviors. (January 2021) - Xie, Zhiyang; Kanvinde, Amit; Chen, Yiyi
Abstract: A unified constitutive model for structural steels is proposed to reproduce commonly observed hysteretic behaviors that are not represented effectively by current models. This model utilizes a concise description of the Bauschinger effect and a virtual boundary surface to formulate a mathematically improved evolution rule for the hardening behavior in the re-yielding and the subsequent stagnation stage. The model includes an explicit discrete update formulation to describe strain range dependence, in a manner that does not require iterative solution. Based on the existing experimental results, this model considers three cyclic mechanisms resulting in the variation of size of the stress boundary surface in different loading histories. For a better description of cyclic behaviors, two new plastic internal variables are proposed to determine the growth of saturated stress in fixed strain range and its temporary decrease under intermediately reverse deformation. For facilitating calibration, evolution rules for this model are established as set of independent equations that may be calibrated separately. Based on the calibrated parameters, the simulation results of proposed model show remarkable agreement with monotonic as well as cyclic testing data of three different steel grades with various measured strength, particularly in the case of irregular loading histories. Graphic abstracts: The simulation results of descending cyclic loading test based on three models and the error analysis of nine cyclic loading protocols (including SP09 random cyclic loading test. Unlabelled Image Highlights: We develop a new model considering various cyclic behaviors of common steels. Hardening stagnation is depicted by simplified formulas of virtual boundary surface. We propose smooth explicit update formulations of memory surface in strain space. Temporary reduced stress in smaller strain under near-fault action is considered. Model is validated under various regular and random loading histories.